Governance and new discounter outlets in Germany - Jürgens, Ulrich (ERDKUNDE, 2012)
In response to public decisions made by planners and policy-makers interest groups have been forming in order to act as a corrective to participatory processes that they do not consider sufficiently transparent. In Germany this has been occurring not only around large-scale projects that generate a lot of media attention, like the plans to upgrade and completely remodel the Central Station of Stuttgart (“Stuttgart21”). Increasingly frequently we also see this in response to local projects at the grassroots level. Discount grocery stores have not been excluded from this development. Because many discount supermarket chains are continuing to expand spatially, “enlightened” customers and affected residents increasingly feel that there is a “glut of discounters.” Community action groups, ad hoc working groups and associations have formed to prevent discounters from opening new outlets or expanding old ones. Or they try to join planners and policy-makers in influencing the process of opening new outlets. New types of governance are developing in which self-help groups are able to give spontaneous and competent answers on short notice to questions that had never before been asked by planners. The fact that there are other coalitions of interest groups that, e.g., try to prevent a discounter from moving out of their local neighborhood, reveals the diversity of peoples’ reactions to developments in discounting. Various examples from Schleswig-Holstein (Germany’s northernmost province) will be used to show the motivations guiding the citizens’ groups. How elitist or “citizen-centered” are their actions? What is their legitimation, whether inherent or self-proclaimed? And what power can they as a group of actors develop to influence planning and policy? To what extent do these groups serve to protect/preserve established types of retail trade? To what extent do other groups contrive to form “coalitions of change” together with discounters (not infrequently by means of “gifts” in the form of infrastructure), in order to put pressure on policy-makers to allow new outlets to be opened?